Awareness, perception and consumption pattern of probiotic dairy products in urban Bengaluru of Karnataka - Ravi Kumar; GP, Shivaswamy; Muniandy Sivaram; Somasekaran Subash; HM, Rashmi; HC, Devaraja (Indian Journal of Dairy Science, 2026)
Growing diversification of food basket with rising incomes and urbanization have created a market niche for probiotic dairy products as they offer potential health benefits beyond basic nutrition. The present study analysed the consumer awareness, perception, and the factors influencing consumer behaviour towards probiotic dairy products in urban Bengaluru. The study used primary data collected from 1,112 dairy foods consumers from urban Bengaluru. While, 53% of respondents were aware of probiotic dairy products, but only 23% actively consumed probiotic dairy products. Probiotic fermented milk was the most preferred probiotic product followed by probiotic yogurt and probiotic curd. Market segmentation analysis revealed that the respondents belonging to the higher age group had a significantly higher consumption of probiotic fermented milk and probiotic yogurt, whereas younger respondents had significantly higher consumption of probiotic ice-cream. Binary logistic regression revealed income as the most influencing factor for consumption of probiotic fermented milk.